O samba na escola e a escola no samba: configurações de uma educação integral popular - Lima, Maria Margareth de (2017)
The thesis The samba in the School and the School in the Samba - configurations of a popular integral education had as main objective to understand the contribution of art/education, from the perspective of popular education, to enable a popular integral education that generates sociocultural participation. The study is justified both by the comprehensiveness of Integral Education, art/education and Popular Education in the national territory, as well as by the need to reflect on the bases being built for the expansion of the fulltime public school of Integral Education in interface with the art / education. The question about the contribution of art/education to integral education towards the configuration of a popular educational practice favorable to the processes of sociocultural participation constitutes the problem issue of research. The work with a qualitative approach results from the case study in two different educational spaces: one, the public school, Monsenhor João Coutinho Municipal School (EMMJC), and the other, the Samba School, Império do Samba Cultural Association (ACIS), both located in the Roger neighborhood, in the city of João Pessoa-PB. The study emphasizes three fields of ideas: 1) enlargement and re-signification of the time and the space of the public school recognizing the educational territory as a democratic extension; 2) art as a sociocultural mediator; 3) the need for the socialization of art conditioned to the production of artistic-aesthetic knowledge, intended in Popular Education and Popular Culture mode. The intersection of ideas that simultaneously articulate Art/Education and Integral Education, based on the foundations and principles of Popular Education, starting with the Freirean ideology, sets up, in this thesis, what is called Popular Integral Education. This approach is based on the thoughts of Paulo Freire, Ana M. Barbosa and Nestor G. Canclini in reciprocity with Carlos Rodrigues Brandão, Antônio Gramsci, Moacir Gadotti and Jaqueline Moll. Between conflicts and contradictions, it is understood that the educational practices of art/education, that occurred in the researched case-units, have approximations with the proper meaning of popular education since they are situated in an unjust social order to the popular classes; in an education of the public teaching, aiming at - even in a fragile way - for a political project of democratic management constituted by subjects of the school and the community, based on the public power; in a community organization of social educators that have the resident culture based on the accumulation of popular power; etc. The research points to some advances and achievements from the point of view of the legal framework and the expansion of the number of full-time schools in the public school of the municipality of João Pessoa, emphasizing that: the perspective of Integral Education is still a challenge at stake; the investigated territory is strongly identified by an artistic-cultural protagonism that is marked by the aesthetics of the culture of tradition; the mobilization of Roger's popular culture contributes to a greater integration between the school culture and the artistic groups of the community culture, increasing the participation of children and young people of the popular class to the movements of artistic culture of their territory. This understanding favors the theoretical and scientific support to the thesis that art/education linked to the conception of integral popular education has a strong power to stimulate socio-cultural participation.